A Scientific Review of Sodium Nitrite and Nitrate: Impact on Human Health and Living Organisms - Fadhil, Lamyaa Abdulridha; Ibrahim, Wijdan Hasan; Abid, Shaimaa A. (Stallion Journal for Multidisciplinary Associated Research Studies, 2025)
Sodium nitrate is an inorganic compound characterized by a white crystalline appearance and high aqueous solubility. Sodium nitrate and nitrite are widely used in numerous industries, notably in food additives, processed meats, fertilizers in agriculture, and pharmaceuticals. While their crucial roles in prolonging shelf life and preventing bacterial growth, their effects on people and other organisms’ health led to serious worries. About 80-85% of the nitrate that humans consume comes from their diet, primarily from vegetables as well as drinking water nitrate. Despite sodium nitrate and nitrite being necessary for many bodily processes, excessive exposure to them has been scientifically attributed to harmful effects on health, especially in the reproductive system, respiratory system, liver, and kidneys. This review attempts to present an analysis of sodium nitrite and nitrate’s impact on different systems in the bodies of organisms, supported by scientific research and literature. In an attempt to minimize health risks of sodium nitrate, individuals should reduce sodium nitrate intake by opting for fresh, unprocessed foods and carefully reading food labels. Regular monitoring and enforcement of sodium nitrate regulations in food and agricultural products are crucial for public health protection and mitigation strategies to reduce its ecological footprint.